Uji Efektivitas Pemberian Trisodium Fosfat (TSP) Untuk Mengeliminasi Burkholderia glumae Penyebab Penyakit Busuk Bulir Bakteri Pada Benih Padi (Oryza sativa L.) - Yushi Mardiana; Sugeng Priyanto (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2025)
Burkholderia glumae infection in rice was first reported in Indonesia in 1987 in Tasikmalaya, West Java, and has since spread to several regions including Sumatra, Java, Bali, Lombok, and South Kalimantan. Seed treatment is one of the recommended methods to prevent and suppress seed-borne pathogens. This study aimed to evaluate the effectiveness of rice seed soaking with Trisodium Phosphate (TSP) solution in eliminating B. glumae using the ELISA method. In addition, physiological seed quality parameters, including germination rate, germination percentage, and seed storability, were also observed. The experiment was conducted from December 2024 to March 2025 in the laboratory and greenhouse of a private company in East Java at an altitude of approximately 220 m above sea level. The results revealed that TSP treatments at concentrations of 2 g/10 ml, 3 g/10 ml, and 4 g/10 ml successfully eliminated B. glumae after three months of storage. Among these, the 2 g/10 ml treatment produced the best performance, yielding higher germination rate and storability compared to 3 g/10 ml and 4 g/10 ml. Furthermore, seed germination and storability on blotter paper medium generally higher than those observed on sand medium. Keywords: Burkholderia glumae, rice seed treatment, trisodium phosphate (TSP), seed germination, seed vigor, seed storage viability